The Identification of the Persian Grammatical Verbs for Teaching to Non-Native Speakers - Zeinab Mohammad Ebrahimi; Shabnam Majidi (مطالعات زبانی و بلاغی)
The present study is an attempt to re-identify grammatical verbs in Persian language, and teaching them to non-Persian speakers based on the CLT approach and within the MP framework. In this regards, two successive objectives are followed: First, revision of grammatical verbs in Persian grammar, explaining the role of each of these verbs, and providing an explanatory analysis for syntactic structures associated with these verbs. Second, teaching grammatical verbs to non-Persian speakers and developing new grammatical texts and rules (such as the position of sentential negation marker) based on this revision. So the main question is: if we put away the traditional descriptions of grammatical verbs, what is the effect of this new linguistic approach on the second language learners? Following a detailed discussion on the Persian grammatical verbs, in the experimental-field research part of study we will try to provide an integrated syllabus within the communicative language teaching approach, based on the theoretical findings of the research. By comparing two groups of Persian learners, i.e. the control group and the experimental group, we will show that teaching grammatical verbs according to the new syllabus leads to facilitation of teaching, learning, and remembering processes, and Persian learners of experimental group will have better and more successful performances, with the average of 5 points higher than the control group.